Ipilmumab and cranial radiation in metastatic melanoma patients: a case series and review. Issue 1 (December 2015) - Schoenfeld, Jonathan; Mahadevan, Anand; Floyd, Scott; Dyer, Michael; Catalano, Paul; Alexander, Brian; McDermott, David; Kaplan, Irving
Abstract Background Ipilimumab improves survival in metastatic melanoma patients. This population frequently develops brain metastases, which have been associated with poor survival and are often treated with radiation. Therefore, outcomes following ipilimumab and radiation are of interest, especially given case reports and animal studies suggest combined treatment may generate abscopal responses outside the radiation field. Findings We reviewed sixteen consecutive melanoma patients who received 1 to 8 courses of radiation, with a sum total of 51, systematically evaluating abscopal responses by following the largest extra-cranial lesion. We also reviewed other series of patients treated with cranial radiation and ipilimumab. Our patients received between 1 and 8 courses of cranial radiation. Four patients received radiation concurrently with ipilimumab. Median survival was 14 months, and 17 months in patients initially treated with SRS. Interestingly, after radiotherapy, there was a 2.8-fold increased likelihood that the rate of extra-cranial index lesion response improved that didn't reach statistical significance (p = 0.07); this was more pronounced when ipilimumab was administered within three months of radiation (p < 0.01). Conclusion Our experience and review of recently published series suggest ipilimumab and cranial radiation is well tolerated and can result in prolonged survival. Timing of ipilimumab administration in relation to radiation may impact outcomes. Additionally, our results demonstrate a trend for favorable systemic response following radiotherapy worthy of further evaluation in studies powered to detect potential synergies between radiation and immunotherapy.